PERAN LITERASI DIGITAL DALAM MENANGKAL HOAX DI MASA PANDEMI (LITERATURE REVIEW) - Erni Novita Sari; Anggi Hermayanti; Nadya Deninda Rachman; Faizi Faizi (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2021)
The Covid-19 pandemic has become a disaster that hit Indonesia and caused a crisis that brought anxiety to the community. Hoax news is easy to spread in the community with the main intermediary, namely digital media. Hoaxes are able to lead public opinion and influence people's mindsets so as to hinder the process of handling Covid-19. The number of hoax cases shows that people's digital literacy skills are still low so that there is no control over the information circulating. Therefore, we conducted this research as a form of concern for the low digital literacy skills of the Indonesian people. This study aims to provide information related to the importance of digital literacy in the use of social media and prevent the spread of hoaxes using the method library research, by utilizing library materials to obtain research data. The results show that digital literacy has an important role in efforts to tackle hoaxes. To improve digital literacy skills, people must develop critical thinking skills and be skeptical or doubt the information received. That way, the public will tend to first examine any information obtained and then judge whether the information is worthy of being accepted and believed to be true or not.